2010
DOI: 10.1063/1.3509404
|View full text |Cite
|
Sign up to set email alerts
|

Heavy noble gas (Kr, Xe) irradiated (111) InP nanoporous honeycomb membranes with enhanced ultrafast all-optical terahertz emission

Abstract: Nanoporous honeycomb membranes on InP (111) surfaces emit ultrafast coherent terahertz pulses under near-infrared optical excitation. Irradiating the membranes with heavy noble gas Kr or Xe ions enhances the terahertz emission. The emission does not vary with in-plane magnetic field rotation and exhibits three-cycle dependence on azimuthal-angle rotation. Both suggest the terahertz source is not transient currents but optical rectification enhanced by the heavy-ion irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In the case of heavy noble gas (Kr, Xe) irradiated (111) InP nanoporous honeycomb membranes, it is found that the terahertz emission is not influenced by an in-plane magnetic field, nor does it show saturation with pump fluence [20]. However, it exhibits a three-cycle dependence on azimuthalangle rotation.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of heavy noble gas (Kr, Xe) irradiated (111) InP nanoporous honeycomb membranes, it is found that the terahertz emission is not influenced by an in-plane magnetic field, nor does it show saturation with pump fluence [20]. However, it exhibits a three-cycle dependence on azimuthalangle rotation.…”
Section: Resultsmentioning
confidence: 99%
“…We developed the photoconductive antenna based on structured InP material and have demonstrated that irradiating nanoporous membranes of (111) InP with heavy noble-gas ions enhances terahertz emission. [2] We developed a technology for deposition contacts/wires upon nanoporous InP thin film structures, see the figures 2, 3. In this way we demonstrate the possibility of fabrication an array of antennas/detectors.…”
Section: Device Fabricationmentioning
confidence: 99%
“…This could be eliminated by placing nonlinear crystal in hollow metallic waveguide structure . The conversion efficiency in optical rectification depends primarily on the material nonlinear coefficient and the phase-matching conditions and various schemes for power enhancement have been reported [Radhanpura et al, 2010;Bugay & Sazonov, 2010;He et al, 2008;Reid et al, 2008].…”
Section: Optical Rectification Based Emittersmentioning
confidence: 99%